Does Turnover Mediate the Relationship between Cooperative Capital and Surplus (SHU)? - Istiqomah Istiqomah; Lilis Siti Badriah (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
Previous studies have indicated that the direct influence of cooperative capital on surplus (SHU) is linear and positive.However, how the capital can increase surplus has not been formally explained.Therefore, in this article the authors try to explain the mechanism of the influence of cooperative capital on surplus (SHU) by including turnover as an intervening variable in the relationship between cooperative capital and surplus.This study used secondary data which consist of cooperative capital, surplus, and business turnover from 43 cooperatives in Indonesia recorded in the annual report of the Ministry of Cooperatives and MSMEs 2016. Cooperative capital, surplus, and trunover are measured in rupiah. Path analysis was employed to analyze the data. The effect of mediation was tested by the causal method developed by Baron & Kenny and the product of coefficient method developed by Sobel. The results indicate that turnover perfectly mediates the relationship between cooperative capital and surplus. This research contributes to the lacking formal logical explanation of the relationship between cooperative capital and surplus, that is, cooperative capital encourages business turnover which eventually increases surplus. Therefore, cooperatives in Indonesia should be able to increase cooperative capital, especially internal capital or supporting external capital. In addition, the government should also encourage efforts to develop and promote cooperatives in Indonesia by making policies to facilitate financial access for cooperatives